Rekonstruksi Paradigma Pemikiran NU: Telaah Metode Istinbat Hukum Islam NU - Ali Mutakin (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2015)
NU society organizations in Indonesia, the largest Islamic world even, NU is a centrist and moderate thinking organitations. Lajnah Bahth al-Masa>’il (LBM) is a religious fatwa institution owned by NU. Operationally it conduct a study of Islamic law to find the legal provisions of the problems that occur in the community (masa'il waqi'iyyah). There has been a paradigm shift in the thinking of qawli madhhab switch to a manhaji madhhab.